Public and private legal, political and philosophical perspectives (Routledge, 2000)
"The public and private distinction is essential to our moral and political vocabularies as it continues to structure our social and legal practices. Public and Private provides an original and multidisciplinary perspective on this distinction which has been at the centre of intense and controversial debates in recent years. The focus of the debates has been on the delineation of acceptable boundaries between the public and private in the economic, social and cultural spheres of modern societies." "What is the nature and scope of citizenship? What are the implications of new reproductive technologies? And what is the fate of state sovereignty in the context of a globalised world economy? At first glance these questions may appear unrelated and yet they all raise underlying and serious concerns regarding the scope and proper boundaries between the public and the private." "Public and Private is a wide-ranging assessment of the changing nature and scope of this demarcation. It will both stimulate the current debate with its original approach and provide a valuable resource for all those interested in the role the public and private play in structuring our societies."--BOOK JACKET.